난황유를 이용한 짚신나물 흰가루병의 방제 - 한기수(Ki-Soo Han); 이정한(Jung-Han Lee); 권영상(Young-Sang Kwon); 배동원(Dong-Won Bae); 김동길(Dong-Kil Kim); 김희규(Hee-Kyu Kim) (Sigmulbyeong yeon'gu, 2008)
We've been involved in collection and domestication of Agrimonia pilosa from 2005 to 2007. We observed agrimony powdery mildew caused by Sphaerotheca aphanis. The powdery mildew developed twice a year, in May to June and mid August to September on whole plants of A. pilosa plants, that is, leaves, stem and floral part. We sprayed the Cooking Oil & Yolk mixture (COY) to control the agrimony powdery mildew. When COY was single-sprayed to control agrimony powdery mildew, its control value was 26.9%. However when it was double-sprayed and triple-sprayed at seven days interval, its control value increased up to 80.8 and 82.7%, respectively. Upon the first spray, symptoms of powdery mildew disappeared within three days and suppressive effect of COY was persisted for only seven days. Thereafter, powdery mildew was relapsed to develop. However, on double to triple sprays, powdery mildew was suppressed more than 28 days after final treatment. Therefore, it is concluded that double spray of COY at seven days interval can control effectively agrimony powdery mildew. 약용작물인 짚신나물에 발생하는 흰가루병의 병원균은 Sphaerotheca aphanis이고, 장마 전 건조기인 $5{\sim}6$월과 8월 말에서 9월까지 2차례 발병하였다. 흰가루병은 잎, 줄기 및 종자 모두에서 관찰 되었다. 난황유 처리에 의한 흰가루병 방제효과는 1회 처리구의 방제가가 26.9%에 불과하였으나, 2회 및 3회 처리구에서는 80.8%, 82.7%의 방제가를 나타내었다. 처리회수에 관계없이 처리 직후에는 흰가루병의 방제 효과가 뚜렷하였으나 1회 처리구에는 처리 7일 후에는 발병이 다시 증가하였던 반면, 2회 및 3회 처리구에는 처리 후 28일까지도 발병이 억제 되는 경향을 보였다. 따라서 짚신나물 흰가루병은 난황유를 7일 간격으로 2회 처리하는 것이 바람직한 방제 방법이라 생각된다.